Strategi Repositioning Bisnis Multi Level Marketing dan Tinjauan Dari Prespektif Syariah - Cahyadi, Iwan Fahri (BISNIS, 2019)
In the last few years this business with the concept of multi level marketing is growing and thriving in Indonesia. In terms of positive law and legal religion, MLM business does not violate the rules. But early in the year 2019, MLM business again got the attention, namely the existence of recommendations of one of Indonesia's largest religious organization. In March 2019 in the closing of the National Congress of scholars conferences Nahdlatul Ulama (NU) at boarding schools Miftahul Huda Al-Azhar, Citangkolo, Banjar, West Java, that MLM business is unlawful. According to Marimin el al., (2016:7) in the journal entitled "business-Level Marketing (MLM) in Islamic view" expressed the basically, legal MLM is determined by the shape of the muamalatnya. If muamalat contained therein is not incompatible with the muamalat Islamic jurisprudence, then the MLM absahlah. However, if muamalatnya is contrary to the Islamic jurisprudence, then the MLM haramlah. Based on the difference of the two opinions it then the purpose of this research is studying and reviewing of legal MLM business MLM businesses and how to repair the company's image over the view that illegitimate MLM business. Qualitative research methods by examining literature, books, journals and other data. From the results of the study that the conclusion that the binis haraam is a type of MLM money games.